Expression of the LspA1 and LspA2 Proteins by Haemophilus ducreyi Is Required for Virulence in Human Volunteers - Janowicz, Diane M. (American Society for Microbiology, 2004)
Haemophilus ducreyi colocalizes with polymorphonuclear leukocytes and macrophages and evades phagocytosis during experimental infection of human volunteers. H. ducreyi contains two genes, lspA1 and lspA2, which encode predicted proteins of 456 and 543 kDa, respectively. Compared to its wild-type parent, an lspA1 lspA2 double mutant does not inhibit phagocytosis by macrophage and myelocytic cell lines in vitro and is attenuated in an experimental rabbit model of chancroid. To test whether expression of LspA1 and LspA2 was necessary for virulence in humans, six volunteers were experimentally infected. Each volunteer was inoculated with three doses (ranging from 85 to 112 CFU) of the parent (35000HP) in one arm and three doses (ranging from 60 to 822 CFU) of the mutant (35000HPΩ12) in the other arm. The papule formation rates were 88% (95% confidence interval [95% CI], 76.8 to 99.9%) at 18 parent sites and 72% (95% CI, 44.4 to 99.9%) at 18 mutant sites (P = 0.19). However, papules were significantly smaller at mutant sites (mean size, 24.8 mm(2)) than at parent sites (mean size, 39.1 mm(2)) 24 h after inoculation (P = 0.0002). The pustule formation rates were 44% (95% CI, 5.8 to 77.6%) at parent sites and 0% (95% CI, 0 to 39.4%) at mutant sites (P = 0.009). With the caveat that biosafety regulations preclude testing of a complemented mutant in human subjects, these results indicate that expression of LspA1 and LspA2 facilitates the ability of H. ducreyi to initiate disease and to progress to pustule formation in humans.